2019
DOI: 10.1111/desc.12847
|View full text |Cite
|
Sign up to set email alerts
|

Comparing statistical learning across perceptual modalities in infancy: An investigation of underlying learning mechanism(s)

Abstract: Statistical learning (SL), sensitivity to probabilistic regularities in sensory input, has been widely implicated in cognitive and perceptual development. Little is known, however, about the underlying mechanisms of SL and whether they undergo developmental change. One way to approach these questions is to compare SL across perceptual modalities. While a decade of research has compared auditory and visual SL in adults, we present the first direct comparison of visual and auditory SL in infants (8-10 months). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…However, in the group of children, the 2-AFC performance did not differ from chance in any condition. This disparity between children and adults’ results is consistent with recent works showing that aSL with non-linguistic materials, as well as with visual stimuli, improves with age ( Arciuli and Simpson, 2011 ; Bertels et al, 2015 ; Lukács and Kemény, 2015 ; Raviv and Arnon, 2018 ; Shufaniya and Arnon, 2018 ; Emberson et al, 2019 ). Nonetheless, it is important to note that the differences in the 2-AFC performance across groups were made at the expense of the absence of reliable signs of learning in the group of children, hence recommending a more nuanced interpretation of the age-related differences in behavioral SL outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in the group of children, the 2-AFC performance did not differ from chance in any condition. This disparity between children and adults’ results is consistent with recent works showing that aSL with non-linguistic materials, as well as with visual stimuli, improves with age ( Arciuli and Simpson, 2011 ; Bertels et al, 2015 ; Lukács and Kemény, 2015 ; Raviv and Arnon, 2018 ; Shufaniya and Arnon, 2018 ; Emberson et al, 2019 ). Nonetheless, it is important to note that the differences in the 2-AFC performance across groups were made at the expense of the absence of reliable signs of learning in the group of children, hence recommending a more nuanced interpretation of the age-related differences in behavioral SL outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Raviv and Arnon (2018) , using auditory syllables and visual figures in auditory (aSL) and visual (vSL) SL tasks modeled from Saffran et al (1996) , showed that while vSL improved in children aged 5–12 years old, aSL did not. This could account for the disparity of results found in the previous studies showing age differences for vSL (e.g., Arciuli and Simpson, 2011 ; Bertels et al, 2015 ), but not for aSL (e.g., Saffran et al, 1997 ; see however Emberson et al (2019) for SL improvements in both modalities). Nonetheless, in a subsequent work, Shufaniya and Arnon (2018) showed that the absence of age differences in the aSL was not due to the sensory modality per se but rather to the type of stimuli used.…”
Section: Introductionmentioning
confidence: 58%
“…Postnatally, the evidence reviewed herein indicates that visual and spatiotemporal sequential learning for co-occurrence frequencies are present at two months (e.g., as in VExP findings and the statistical learning study by Kirkham et al 2002) and older (e.g., by nine months; Emberson, Misyak, Schwade, Christiansen, and Goldstein 2008), with further statistical learning of regularities within visual arrays documented at nine months (Fiser and Aslin, 2002).…”
Section: Early Perceptual Developmentmentioning
confidence: 88%
“…One notable form of learning is statistical learning (SL)the process of using probabilistic co-occurrence to group elements present in the environment. SL is operational in a rudimentary form in neonates (Bulf, Johnson, & Valenza, 2011;Teinonen, Fellman, Näätänen, Alku, & Huotilainen, 2009), is robustly observed across different modalities during the first year of life (Emberson, Misyak, Schwade, Christiansen, & Goldstein, 2019;Kirkham, Slemmer, & Johnson, 2002;Saffran, Aslin, & Newport, 1996), and at least in the visual domain continues to develop throughout childhood (Arciuli & Simpson, 2011;Raviv & Arnon, 2018). Studies that report associations between SL and other cognitive skills (e.g., spoken language, reading) suggest that SL could be an important component of human cognition that varies across individuals (e.g., Arciuli & Simpson, 2011;Conway, Bauernschmidt, Huang, & Pisoni, 2010;Frost, Armstrong, & Christiansen, 2019).…”
Section: Introductionmentioning
confidence: 99%